A New High‐Entropy Alloy of Al–Fe–Co–Ni–Cu Possessing Single Face‐Centered Cubic Crystal Structure and Excellent Mechanical Properties at Room Temperature. Issue 8 (24th February 2021) - Das, Sujit; Nishad, Saurabh Kumar; Robi, P.S
Abstract : A new powder combination of Al10 (FeCoNiCu)90 is selected and verified for the potential to form solid solutions or else bulk metallic glasses (BMGs) in the alloy based on Guo et al.'s conditions and mismatch entropy criterion. The powder combination satisfies the above criteria to crystallize in solid‐solution phases and inhibits the formation of BMGs in the alloy. The alloy is fabricated by mechanical alloying of the powder mixture followed by sintering. A homogeneous powder mixture is obtained after ball milling for 80 h. The 80 h‐milled powder is crystallized in two face‐centered cubic (FCC) phases. The lattice parameters of the FCC1 and FCC2 phases are 3.60 Å and 5.21 Å, respectively. The microstructure of the alloy ingot reveals spinodal decomposition. The alloy ingot crystallizes in a single‐FCC structure. The lattice parameter of the corresponding FCC structure is determined as 3.66 Å. The compression test of the alloy ingot at room temperature reveals that the 0.2% offset yield stress of the high‐entropy alloy (HEA) is as high as 308 MPa. The compressive stress at 40% strain of the HEA is 1406 MPa. The overall Vickers hardness and density of the alloy ingot are 160 ± 14 HV0.5 and 7.7 g cm −3, respectively. Abstract : A high‐entropy alloy of Al10 (FeCoNiCu)90 is processed by arc melting and sintering. The ball‐milled powder crystallizes in two face‐centered cubic (FCC) phases, whereas the alloy ingot crystallizes in a single‐FCC phase. The spinodal decomposition occurs in the alloy ingot. The alloy shows fine compressive strength and hardness.